2011
DOI: 10.1007/s00404-011-2098-0
|View full text |Cite
|
Sign up to set email alerts
|

Hormone replacement therapy leads to increased plasma levels of platelet derived microparticles in postmenopausal women

Abstract: Higher concentrations of microparticles derived from (activated) platelets/megacaryocytes were present in postmenopausal women taking hormonal replacement therapy. This finding indicates a procoagulant state in these women and might play a role in the development of venous side effects. In contrast, levels of endothelial cell-derived microparticles did not differ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…In line with this conclusion, we found the highest counts of CD61-exposing MP in premenopausal women who took estrogen-containing contraceptives, even though the number of investigated women is small and limits the validity of our data. But the idea of a relevant influence of female hormones on the plasma level of CD61+ MP is supported by recent published data from our group: this subtype of plasma MP is higher in postmenopausal women with hormone replacement therapy compared to those without hormone replacement therapy [28]. The general relevance of estrogens becomes evident by the fact that women have higher mean counts of platelets as well as of CD61-exposing MP – probably mainly derived from megakaryocytes – than men [29].…”
Section: Discussionsupporting
confidence: 68%
“…In line with this conclusion, we found the highest counts of CD61-exposing MP in premenopausal women who took estrogen-containing contraceptives, even though the number of investigated women is small and limits the validity of our data. But the idea of a relevant influence of female hormones on the plasma level of CD61+ MP is supported by recent published data from our group: this subtype of plasma MP is higher in postmenopausal women with hormone replacement therapy compared to those without hormone replacement therapy [28]. The general relevance of estrogens becomes evident by the fact that women have higher mean counts of platelets as well as of CD61-exposing MP – probably mainly derived from megakaryocytes – than men [29].…”
Section: Discussionsupporting
confidence: 68%
“…Lowered levels are described in postmenopausal women with decreased estradiol levels, hormone replacement therapy reverses this effect, though (222,223).…”
Section: Distribution Of Pl-evsmentioning
confidence: 99%
“…Data in the literature indicate that exogenous female hormones significantly increase the MP production from platelets and granulocytes in post-menopausal women [38]. Thus, because of the thrombogenicity of hormonal contraception, it was expected that higher MP activity would be found in the OC(+) group than in the OC(-) group, but in the current study, the reverse was found.…”
Section: Discussionmentioning
confidence: 45%